The place and position of Kurdish women's clothing in national identity - Ali, Asst.L. Sharmin Wali (Sulaimani Journal for Humanities, 2025)
Clothing is the key to the unique revelation of the individual Among all nations, every society has some kind of clothing that connects it to its society and culture; In this regard, the Kurdish nation as the largest stateless nation in the world, has its own clothing in many different types, designs and styles that reflect the topography and geographical location of Kurdistan This study is a scientific attempt to answer the question: To what extent is clothing seen as a symbol and identity? What are the cultural signs behind Kurdish clothing and what meanings and evidence do they contain? The importance of this study lies in; Being the first scientific and academic attempt in Kurdish in the field of anthropology on clothing, it will also be an incentive to pay attention to clothing as an important symbol for the Kurds, as a stateless nation. Therefore, the overall purpose of this research is to show the reality of Kurdish women's clothing from the perspective of Kurdish experts, as well as the influence of ideology on clothing as a symbol of national identity and even the color of Kurdish women's clothing is reflected in our society.
Keywords: Position; Clothes; Identity; National identity